Economic Integration between the EU and the CEECs: A Sectoral Study - Francesca DiMauro (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2001)
Economic integration between the EU and the CEECs has proceeded at high speed over the 90's, with the main channels of such integration being trade and FDI. Some authors believe that the `commercial transition?is now complete and that a new, deeper phase of integration has started, with growing flows of FDI in the region. Following a gravitytype approach, in this paper I tackle two difficult issues surrounding the EU-CEECs integration: has FDI in the CEECs region substituted EU exports, therefore hfirming employment at home? Has FDI in the CEECs region been redirected away from similarly attractive countries, such as Spain and Portugal? By using a unique database on FDI broken down by country and by sector, which allows more detailed qualifications than possible in previous work, the answers to these two questions appear to be negative.
Keywords: F15; F21; F23; 330; Foreign Direct Investment; Economic integration; Gravity Model; Direktinvestition; EU-Europäisch; Gravitationsmodell; Entwicklungskonvergenz; Osteuropa